Penile Microvascular Damage in Metabolic Syndrome: Implications for Early Sexual Dysfunction - I Made Oka Negara (PT FORMOSA CENDEKIA GLOBAL, 2026)
Metabolic syndrome is a global health issue characterized by obesity, insulin resistance, dyslipidemia, and hypertension, which increase the risk of vascular complications. This study aims to analyze the relationship between metabolic syndrome and penile microvascular damage and its implications for early sexual dysfunction. A qualitative approach with a systematic literature review design was used, drawing data from PubMed, Scopus, Google Scholar, and ScienceDirect, and analyzed through thematic analysis. The findings show a strong association mediated by endothelial dysfunction, oxidative stress, chronic inflammation, and impaired nitric oxide bioavailability. These mechanisms reduce penile blood flow and trigger early erectile dysfunction as an early marker of systemic vascular disease. Early detection and intervention are essential to prevent cardiovascular complications and improve clinical outcomes.